Residual Antibiotics in Decontaminated Human Cardiovascular Tissues Intended for Transplantation and Risk of Falsely Negative Microbiological Analyses - Buzzi, Marina; Guarino, Anna; Gatto, Claudio; Manara, Sabrina; Dainese, Luca; Polvani, Gianluca; Tóthová, Jana D'Amato (PLOS ONE, 2014)
We investigated the presence of antibiotics in cryopreserved cardiovascular tissues and cryopreservation media, after tissue decontamination with antibiotic cocktails, and the impact of antibiotic residues on standard tissue bank microbiological analyses. Sixteen cardiovascular tissues were decontaminated with bank-prepared cocktails and cryopreserved by two different tissue banks according to their standard operating procedures. Before and after decontamination, samples underwent microbiological analysis by standard tissue bank methods. Cryopreserved samples were tested again with and without the removal of antibiotic residues using a RESEP tube, after thawing. Presence of antibiotics in tissue homogenates and processing liquids was determined by a modified agar diffusion test. All cryopreserved tissue homogenates and cryopreservation media induced important inhibition zones on both Staphylococcus aureus- and Pseudomonas aeruginosa-seeded plates, immediately after thawing and at the end of the sterility test. The RESEP tube treatment markedly reduced or totally eliminated the antimicrobial activity of tested tissues and media. Based on standard tissue bank analysis, 50% of tissues were found positive for bacteria and/or fungi, before decontamination and 2 out of 16 tested samples (13%) still contained microorganisms after decontamination. After thawing, none of the 16 cryopreserved samples resulted positive with direct inoculum method. When the same samples were tested after removal of antibiotic residues, 8 out of 16 (50%) were contaminated. Antibiotic residues present in tissue allografts and processing liquids after decontamination may mask microbial contamination during microbiological analysis performed with standard tissue bank methods, thus resulting in false negatives.